Psilocybin-assisted psychotherapy as a potential treatment for eating disorders: a narrative review of preliminary evidence - Elena Koning; Elisa Brietzke (Trends in Psychiatry and Psychotherapy)
Abstract Eating disorders (ED) are a group of potentially severe mental disorders characterized by abnormal energy balance, cognitive dysfunction, and emotional distress. Cognitive inflexibility is a major challenge to successful ED treatment and dysregulated serotonergic function has been implicated in this symptomatic dimension. Moreover, there are few effective treatment options and long-term remission of ED symptoms is difficult to achieve. There is emerging evidence for the use of psychedelic-assisted psychotherapy (PAP) for a range of mental disorders. Psilocybin is a serotonergic psychedelic that has demonstrated therapeutic benefit in a variety of psychiatric illnesses characterized by rigid thought patterns and treatment resistance. The current paper presents a narrative review of the hypothesis that psilocybin may be an effective adjunctive treatment for individuals with EDs, based on biological plausibility, transdiagnostic evidence, and preliminary results. Limitations of the PAP model and proposed future directions for its application to eating behavior are also discussed. Although the literature to date is not sufficient to propose the incorporation of psilocybin in the treatment of disordered eating behaviors, preliminary evidence supports the need for more rigorous clinical trials as an important avenue for future investigation.